ON THE DIRECT PROBLEM AND SCATTERING DATA FOR A SINGULAR SYSTEM OF DIFFERENTIAL EQUATIONS WITH DISCONTINUOUS COEFFICIENTS - DARWISH, A. A. (Tamkang Journal of Mathematics, 1996)
A system of Sturm-Liouville differential equations of order n with a density matrix function is considered. The direct problem of the considered system is studied and hence the scattering data of the problem is obtained.